Canadian Film and Video : a Bibliography and Guide to the Literature. - Lerner, Loren (Book collections on Project MUSE., 1997)
This bibliography guides and supports the work of film historians and practitioners, media librarians and visual curators, students and researchers, and members of the general public with an interest in film and video.